Empirical study on the influence of facilitating condition on the use of e-government service among SMES in Saudi Arabia - Hassan, Syahida; Ibrahim, Huda (Global Academic Excellence, 2018)
The proposed empirical study investigates the critical role of facilitating condition on the use of e- government services among SMEs in Saudi Arabia. The data were collected and analyzed through using SEM and AMOS software. The finding indicates that facilitating condition has no effect on the use of e-government services among SMEs employees in Saudi Arabia even though most of the previous studies have had indicated that this variable play significant role in the use of e government services. Thus, the results is differ from other studies which might led to discover that the context and the sector play considerable effect on the results. The main objective of this study is to identify the factors that influence the use behavior of e-government service among employees of SMEs in Saudi Arabia. Despite various constraints to the study, the results have been encouraging, as it has managed to throw some lights on e-government service within SMEs in Saudi Arabia. This study proposed an integrated model between technology readiness index (TRI) and the unified technology and accepted use technology 2 (UTAUT2) and found that facilitating condition play an important role to determine the use behavior of e-government service of SMEs.